BASIC FACTORS OF MARKET CONCENTRATION - V. Fyliuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper systemizes factors which reinforce trends towards market concentration in all economic systems. These factors include factors related to the general changes in economic environment such as globalization of the world economy, state structural and taxation policies, cycle of economic development and changes in consumer demand. They also include factors related to competition (intensification of competition, companies’ desire to monopolize market and present market structure) and scientific progress (improvement of technical level of production and formation of new technological structures). Specific factors depend on company’s location and the area where it operates. They include political, geophysical, legal and other factors. In Ukraine intensification of market concentration processes was caused by leftovers of planned economy especially by the susceptibility to create huge production unions, agricultural and territorial-production complexes and by specificity of transition of Ukrainian economy to the market system (for instance, convergence of insurance and banking markets, high inflation rates, etc.)